A State of Uncertainty: An Analysis of Recent State Legislative Proposals to Regulate Preventive Services in the United States - Maxim Gakh JD, MPH; Cody Cris; Prescott Cheong MPH; Courtney Coughenour PhD (SAGE Publishing, 2019)
This policy brief examines preventive services state legislation trends in the United States during uncertainty regarding the Affordable Care Act (ACA), which requires certain coverage of 4 evidence-based preventive services categories without additional patient costs under §2713. We used a legal mapping approach to search for and analyze state legislation related to preventive services proposed or enacted over a 25-month period of ACA uncertainty. We screened 1231 bills and coded the 76 screened-in bills. Next, we determined their characteristics and examined trends. Bills originated in 28 states, and 69.7% were not enacted. Only 3.9% contained requirements contingent on ACA modifications. About 56.6% referenced services covered by §2713, but usually not entire §2713 categories. Bills also mentioned preventive services in general (53.9%) and services outside §2713's scope (21.1%). About 55.3% applied to private insurance, and 75.0% only to one patient group. Bills generally promoted access, and 51.3% specifically prohibited cost-sharing. But 26.3% of the bills limited access to preventive services. State-level legislation targets preventive services, usually expanding, but sometimes limiting, access. Most bills single out specific services without fully incorporating evidence-based recommendations. State legislation may therefore promote access to preventive services but can favor certain services, deviate from experts' recommendations, and increase nationwide variability. State legislation can function as an important lever for access to preventive services across patient groups. This may be especially important during uncertainty about federal policy. However, the design of state-level proposals is critical for maximizing access to preventive services.